Enhanced Cytotoxicity for Colon 26 Cells Using Doxorubicin-Loaded Sorbitan Monooleate (Span 80) Vesicles - Keita Hayashi, Tsuyoshi Tatsui, Toshinori Shimanouchi, Hiroshi Umakoshi (International Journal of Biological Sciences, 2013)
Span 80 (sorbitan monooleate) vesicles behaved differently from conventional phospholipid vesicles (liposomes) because the former had a more fluid interface. After doxorubicin hydrochloride (DOX) was encapsulated into the Span 80 vesicle (loading efficiency: 63 %), DOX-loaded Span 80 vesicles (DVs) were thereafter added to Colon 26 cells. It was suggested, from the flow cytometric analysis and confocal laser microscopic observation, that DVs directly deliver DOX into the cytoplasm of Colon 26 cells. DVs showed the different delivery manner from the DOX-loaded liposomes (DLs). It is considered that the difference of delivery manner between DVs and DLs resulted in the difference of cytotoxicity (IC50); i.e. IC50 values for DVs and DLs were 5 and > 30 μM, respectively. The results obtained herein would give the fundamental findings which can contribute to the improvement of formulation of conventional liposome-based carrier and its cytotoxicity.